ULTRASONIC MEDIATED LIPID EXTRACTION FROM CHLORELLA VULGARIS AGAINST CONVENTIONAL METHODS WITH IONIC LIQUIDS AS ADDITIVE - KRISHNAN, SOORIDARSAN (2019)
Microalgae are photosynthetic unicellular microorganisms containing large amounts of lipids which have been proven to be highly useful in various fields including pharmaceuticals, food industry and in renewable energy.